Effect of fermented food consumption on biochemical parameters and adipokines levels - Gezginç, Yekta; Marancı, Canan (Progress in Nutrition, 2018)
Background/aims: The aim of this study was to determine how fermented food consumption affected the presence of changes in Adipokines levels such as apelin-13, leptin and adiponectin, besides some biochemical parameters. Methods: For this purpose, 23 healthy women and men were selected. Blood samples taken from 12 female and 11 male whose ages ranged between 19 and 25 years before and after kefir consumption, and apelin-13, leptin and adiponectin were analyzed from adipokines besides routine biochemical parameters. Results: The decrease in LDL cholesterol levels which are an indicator of endogenous cholesterol production was found significant (p <0,05), similarly decrease in triglyceride levels and MDA levels which are defined as oxidant stress indicators were significant, when adipokines were examined, it was determined that there was no significant change in adiponectin and a significant increase in apelin-13 and leptin levels from the point of kefir and yoghurt use. Conclusions: It was considered that the presence of beneficial effects on health of kefir as fermented product was revealed. It is thought that this work will be supported by extensive studies to be carried out in the future.